Activity of Extract Seed Moringa Oleifera on Gene Expression of (EFB1) Gene in Candida dubliniensis Isolated from oral Candidiasis to Cancer Patients - Zahraa Khudhair Abbas Al-Khafaji1 Farqad Abdulelah Ali AL-Janahi2 , Al-karrar Kais abdul Jaleel Duai (Indian Journal of Forensic Medicine & Toxicology, 2020)
Gene expression of EFB1 gene in yeast Candida dubliniensis isolated from oral candidiasis in cancerpatients was detected using by R-time PCR for some isolates before and during the yeast infection of theepithelial cells. The results showed a high rate of gene expression of T2 ( 42.104 ± 6.533) and a significantdifference at the probability level P>0.01 compared with the treatment was c (1.034 ± 0.126 ) and the useof the Moringa oleifera extract was 25% to evaluate its effect on the gene expression (ALS1) before andduring yeast infection of epithelial cells. The results showed that the gene expression of T1 was decreasedby ( 0.129 ± 0.021) compared to (C) value (1.034 ± 0.126) .As for the T2 treatment was gene expression at a rate (42.104 ± 6.533) high Compared with T3 treatment inwhich gene expression dropped at a rate (22.143 ± 4.176 ) and with a significant difference at the level ofthe probability of P ? 0.01.